Sistem Pelayanan Kasir Dengan Pemberian Salam Dan Pendeteksi Pengunjung Berbasis Arduino (Studi Kasus : PT.HDI) - Wahyu Diantoro; Maulana Ardhiansyah (CV. Multi Kreasi Media, 2023)
Cashier service is an important part of every sales transaction process that deals directly with consumers. Where Services A cashier must be able to serve consumers feel comfortable. Although the main task is to receive transactions, it cannot be separated from service. As is the case with PT.HDI Center Bintaro's stockist, where greeting services for consumers still have to be spoken directly by a cashier based on the statement above, the application of the Arduino Uno-based Ir Obstacle sensor at PT. HDI Center Bintaro can speed up the greeting service process to visitors, besides that it can record visitors who arrive accurately and quickly. In the results of the trial system that has been completed and successfully created, the system will soon be implemented at PT.HDI Center Bintaro.